The Metamorphosis of Home Concept in Capitalist Imperialism: A Critical Analysis of Death of Salesman by Arthur Miller (Global Journal of Human-Social Science, 2019)
Death of Salesman by Arthur Miller delineates the imperialistic aggregation of money which leads to the tragic dénouement of a life. Money like imperialist controls everybody's everything in this play. How much does anybody earn? -it is the main criteria of success in this play. This structure of society treats human being like a disposed of commodity, after using it is thrown out. Willy Loman, a man of sixty, becomes valueless in his company at this age, though it considers his worth in his youth. Materialistic sense devoid of humanitarian values entangles him tightly. He is always looking for a home with optimism which turns into pessimism with his tragic death for giving financial security for his family. His visionary ideas and all emotional needs by the blow of imperialistic tactics of money face treats continuously for money-making weapons. This paper aims at how his continuous looking for a home without true mental happiness with love and sympathy makes a metamorphosis of home built by the wall of money and turns into an ending of life-giving uncertainty of any security to his family.
Keywords: capitalist imperialism; home